Umbilical Artery Thrombosis After Selective Termination in Dichorionic Diamniotic Twin Pregnancy: A Case Report - Liu H; Zeng Z; Liao H; Hu Q; Yu H (Dove Medical Press, 2023)
Hongyan Liu,1,2 Zhaomin Zeng,1,2 Hua Liao,1,2 Qing Hu,1,2 Haiyan Yu1,2 1Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of ChinaCorrespondence: Haiyan Yu, Department of Obstetrics and Gynecology, West China Second University Hospital, No. 20, 3rd Section, South Renmin Road, Chengdu, Sichuan, 610041, People's Republic of China, Email fanjy422@163.comIntroduction: Umbilical artery thrombosis is a rare complication associated with poor perinatal outcomes. The incidence of umbilical artery thrombosis in pregnancy is estimated from 0.0025% to 0.045%. Prenatal screening and diagnosis of umbilical artery thrombosis is usually performed by ultrasonography. Up to now, no treatment consensus has been achieved.Case Presentation: We present a case of dichorionic diamniotic twin pregnancy complicated with selective termination of one twin with lymphoid cystic tumor at 14 weeks and 2 days of gestation and the alive twin occurred single umbilical artery thrombosis at 35 weeks and 6 days of gestation. The emergency cesarean section was performed after emergency admission. A healthy male baby was delivered weighing 2690g with Apgar scores of 10 and 10 at 1 and 5 minutes, respectively, whereas the dead fetus weighed 10 g. Thrombosis was observed throughout one of the umbilical artery of the alive fetus. The woman and the infant are followed up closely and both in good condition.Conclusion: The number and morphology of umbilical arteries should be carefully observed during pregnancy. Individualized management of umbilical artery thrombosis should be based on clinical conditions. Timely termination of pregnancy if necessary could be suitable to improve adverse pregnancy outcomes.Keywords: umbilical artery thrombosis, adverse pregnancy outcome, twin pregnancy